IMMUNOPATHOGENESIS OF MYASTHENIA GRAVIS (REVIEW) - E. D. Gasymly (Архивъ внутренней медицины)
Myasthenia gravis is a progressive autoimmune disease, which characterized by the production of antibodies to the structures of the neuromuscular junction. High clinical heterogeneity of autoimmune myasthenia, initiating the flow, increases the urgency of studying its pathogenesis, searching for specific methods of marker diagnostics, developing algorithms for predicting the features of the development of the disease. At the present time, there are different approaches to the study of the etiology and pathogenesis of the disease, which include both serological, biochemical, genetic, etc. theory of the development of the disease. For decades, research has been carried out to find new pathogenetic links in myasthenia gravis. Today was described a number of antibodies such as for muscarin (MuSK), ryanodine receptors, to titin, lipoprotein bound receptor 4, cortactin, etc.). The serological diagnosis of myasthenia gravis has been used as a «gold standard» in clinical practice. The prognostic criteria describing the course of myasthenia gravis and the type of antibodies isolated in the blood serum of the patient. Also, already have been developed mechanisms of failure of autotolerance, triggering the production of antibodies to their own structures, and their genetic bases are also described. Thanks to the development of biotechnological methods, the researchers were able to identify the subtype of lymphocytes involved in the development of myasthenia gravis. Isolation of individual subpopulations of lymphocytes also became available. Researchers continue to search for new targets, allowing to improve diagnostics, to develop new directions in the therapy of the disease. However, despite the active study of various mechanisms for the development of myasthenia gravis, many unresolved problems still remain. The article describes briefly the main mechanisms studied in the development of myasthenia gravis, which in turn facilitates understanding of complex mechanisms of pathogenesis.